Renaming Enkeldoorn: Whiteness, place, and the politics of belonging in Southern Rhodesia. (July 2022) - Bishi, George; Mujere, Joseph; Mamvura, Zvinashe
Abstract: By examining the 1935 attempt by the Enkeldoorn Town Management Board in Southern Rhodesian (modern-day Zimbabwe) to change the town's name to Charter, this article examines the contentious politics of place renaming and its intersection with struggles over public memory, identity, and belonging. It examines how the Afrikaner population, which was a component of Southern Rhodesia's white society, campaigned against the intended renaming of Enkeldoorn Town and fought to safeguard their identity by retaining the Afrikaans name Enkeldoorn. This article adds to Southern Africa's increasing literature on white identities, whiteness, and white societies by illuminating divisions within the Southern Rhodesian settler community based on ethnic differences between English and Afrikaans-speaking whites. Additionally, it examines the significance of place names as embodiments of a people's collective memory and legacy building, contributing to current discussions about toponymic commemorative practises by connecting them to broader concepts such as the social construction of places and collective memory. Place renaming is usually controversial since place names encapsulate a people's cultural experience and collective heritage. Therefore, place renaming becomes a point of contention between colonised peoples, affected social groups, and the state or socio-politically-dominant parties wanting to impose new names. Highlights: Explores the historical geographies of British-Afrikaner settler relationships and whiteness in South Rhodesia. Argues that place naming is a form of memorialisation. Shows how subordinate groups may contest the hegemonic geographies of dominant groups. Explores the post-colonial politics of place re-naming.